MANAJEMEN MADRASAH DALAM PERSPEKTIF ISLAM - Muhammad Madarik (CENDEKIA: Jurnal Studi Keislaman, 2016)
If management is a process, then the organization is a framework, structure or container of people to cooperate. Thus, management is a step in achieving this goal through the potential of others were accommodated in an organization. Therefore, it is clear that the relationship between the management and organization are like two sides of a coin. In the view of Islam there are four principles for developing management, namely: 1) the truth, 2) honesty, 3) openness, and 4) expertise. Islamic educational institutions began to develop in Indonesia since before independence of Indonesia in the early 20th century AD with the establishment of formal-Islamic madrasas. It was madrasah is already running in a long time and has a long history, but the perceived Islamic education is still excluded from the National Education System up to 3 Ministers decree issued in 1975 that most people will appreciate that Islamic education received state recognition. Therefore, the management of educational institutions of Islamic-based management is a thing that is not negotiable. In fact, the principles of education in normative Islam did not collide with the concept of management.